Uncontrolled Citrus psorosis virus infection in Citrus sinensis transgenic plants expressing a viral 24K-derived hairpin that does not trigger RNA silencing - Reyes Martinez, Carina Andrea (2016)
Citrus psorosis virus (CPsV) is the causal agent of psorosis disease of citrus. Pineapple sweet orange plants were transformed with a hairpin construct derived from the viral 24k gene (lines ihp24K). Contrary to expectations, these lines did not trigger efficient RNA silencing, and when infected with CPsV they showed a phenotype of exacerbated symptoms with a persistent and homogeneous infection without the recovery observed in non-transgenic plants. Ihp24K lines did not behave similarly when challenged with Citrus tristeza virus. All these results indicate that hypersusceptibility is likely related to the specific action of 24K-derived hairpin over CPsV multiplication.